Intra-Pituitary Administration Revisited: Development of a Novel in Vivo Approach to Investigate the Ovine Hypophysis - Taylor, W. Andrew (2011)
The anterior pituitary gland regulates physiological processes via the secretion of hormones, which are under the control of factors produced either in the hypothalamus or the pituitary gland itself. Studies investigating how the pituitary gland functions have employed both in vitro and in vivo approaches. Although in vitro analysis has the advantage that it is pituitary specific, the results may be incomplete because the tissue is isolated from other physiological inputs that could affect function under natural conditions. Without vascular input, such studies are inherently of short duration. Conversely, in vivo experiments that rely upon systemic hormone injections require high doses, are non-target specific and the precise hormone concentrations reaching the pituitary gland are difficult to control. Intracerebroventricular hormone infusions are reliant on assumptions that factors are transported to the pituitary gland from the cerebrospinal fluid and are without cerebral effects. Here we describe an innovative method to investigate anterior pituitary function in conscious sheep by direct infusion of peptides into the pituitary tissue surrounding the hypophyseal portal blood vessels. This approach is an adaptation of the hypophyseal portal cannulation technique whereby an indwelling cannula provides direct access to the rostral aspect of the adenohypophysis. Peptide infusions were achieved by insertion of a needle through the implanted cannula such that it penetrated the pituitary. Using this technique, infusion of TRH (17ng/1μl/min for up to 6h) induced a sustained rise in systemic prolactin levels that lasted for the duration of the infusion.